Recurrent Episodes of Pericardial Effusion as Isolated Manifestation of Tuberculosis: Case Report - Westin, Oscar; Qayyum, Abbas A. (Current Medical Imaging, 2019)
Background: Recurrent episodes of isolated pericardial effusion due to tuberculosis, leading to reduced Left Ventricle Ejection Fraction (LVEF), are uncommon. Methods: This is a case report of a previously healthy 32-years old male with tuberculous induced pericardial effusion as isolated manifestation. The only known exposure of tuberculosis was a brother with whom the patient did not have physical contact during the last year. The pericardial effusion repeatedly appeared after being drained a total of three times. Due to recurrent episodes of pericardial effusion, severe thickening of the pericardium, pericardial adherences and increasing affection on the heart, pericardiectomy was ultimately performed. Results: Biochemical examination, chest X-ray, computed tomography of thorax and abdomen and cytology report did not reveal any signs of malignancy, connective tissue disease or other infections including extra-pulmonary/pulmonary tuberculosis. However, the pericardial biopsy was Polymerase Chain Reaction positive (PCR) for tuberculosis DNA and showed granulomatous inflammation with necrosis. After 6 months anti-tuberculous therapy, biochemical parameters, LVEF and the clinical condition of the patient were normalized. Conclusion: Tuberculosis can be difficult to diagnose when it only manifests as pericardial effusion especially if the time for exposure is long before the appearance of symptoms and admission.
Keywords: Constrictio cordis